Preventing Acute Malnutrition among Young Children in Crises: A Prospective Intervention Study in Niger - Langendorf, Céline (Public Library of Science, 2014)
BACKGROUND: Finding the most appropriate strategy for the prevention of moderate acute malnutrition (MAM) and severe acute malnutrition (SAM) in young children is essential in countries like Niger with annual “hunger gaps.” Options for large-scale prevention include distribution of supplementary foods, such as fortified-blended foods or lipid-based nutrient supplements (LNSs) with or without household support (cash or food transfer). To date, there has been no direct controlled comparison between these strategies leading to debate concerning their effectiveness. We compared the effectiveness of seven preventive strategies—including distribution of nutritious supplementary foods, with or without additional household support (family food ration or cash transfer), and cash transfer only—on the incidence of SAM and MAM among children aged 6–23 months over a 5-month period, partly overlapping the hunger gap, in Maradi region, Niger. We hypothesized that distributions of supplementary foods would more effectively reduce the incidence of acute malnutrition than distributions of household support by cash transfer. METHODS AND FINDINGS: We conducted a prospective intervention study in 48 rural villages located within 15 km of a health center supported by Forum Santé Niger (FORSANI)/Médecins Sans Frontières in Madarounfa. Seven groups of villages (five to 11 villages) were allocated to different strategies of monthly distributions targeting households including at least one child measuring 60 cm–80 cm (at any time during the study period whatever their nutritional status): three groups received high-quantity LNS (HQ-LNS) or medium-quantity LNS (MQ-LNS) or Super Cereal Plus (SC+) with cash (€38/month [US$52/month]); one group received SC+ and family food ration; two groups received HQ-LNS or SC+ only; one group received cash only (€43/month [US$59/month]). Children 60 cm–80 cm of participating households were assessed at each monthly distribution from August to December 2011. Primary endpoints were SAM (weight-for-length Z-score [WLZ]<−3 and/or mid-upper arm circumference [MUAC]<11.5 cm and/or bipedal edema) and MAM (−3≤WLZ<−2 and/or 11.5≤MUAC<12.5 cm). A total of 5,395 children were included in the analysis (615 to 1,054 per group). Incidence of MAM was twice lower in the strategies receiving a food supplement combined with cash compared with the cash-only strategy (cash versus HQ-LNS/cash adjusted hazard ratio [HR] = 2.30, 95% CI 1.60–3.29; cash versus SC+/cash HR = 2.42, 95% CI 1.39–4.21; cash versus MQ-LNS/cash HR = 2.07, 95% CI 1.52–2.83) or with the supplementary food only groups (HQ-LNS versus HQ-LNS/cash HR = 1.84, 95% CI 1.35–2.51; SC+ versus SC+/cash HR = 2.53, 95% CI 1.47–4.35). In addition, the incidence of SAM was three times lower in the SC+/cash group compared with the SC+ only group (SC+ only versus SC+/cash HR = 3.13, 95% CI 1.65–5.94). However, non-quantified differences between groups, may limit the interpretation of the impact of the strategies. CONCLUSIONS: Preventive distributions combining a supplementary food and cash transfer had a better preventive effect on MAM and SAM than strategies relying on cash transfer or supplementary food alone. As a result, distribution of nutritious supplementary foods to young children in conjunction with household support should remain a pillar of emergency nutritional interventions. Additional rigorous research is vital to evaluate the effectiveness of these and other nutritional interventions in diverse settings. TRIAL REGISTRATION: ClinicalTrials.gov NCT01828814 Please see later in the article for the Editors' Summary